NUSYŪZ SUAMI DALAM QS. AN-NISĀ’ [4]:128: ANALISIS TAFSIR AL-MUNĪR WAHBAH AZ-ZUHAILI DAN IMPLIKASINYA TERHADAP HUKUM KELUARGA ISLAM - Nur Azzahroni, Trisni; Fatirahwahidah; Syahrul Mubarak; Akib, Nasri (EL-MAQRA', 2025)
This study aims to examine the concept of nusyuz committed by husbands as presented in QS. An-Nisā’ [4]:128 through an analysis of Wahbah Az-Zuhaili’s interpretation in Tafsir al-Munīr and a comparison with the interpretations of al-Qurṭubī, Ibn Kathīr, and Quraish Shihab. This research employs a qualitative library-based method with analytical approaches integrating linguistic, historical, legal, and maqāṣid al-sharī‘ah perspectives. The findings reveal that Az-Zuhaili defines nusyuz by husbands as a form of negligence, emotional withdrawal, indifference, and harmful behavior that violates the principle of al-mu‘āsyarah bil-ma‘rūf (harmonious marital conduct). His interpretation corrects the classical tendency to associate nusyuz primarily with wives. Compared to other exegetes, Az-Zuhaili offers a more comprehensive and contextually relevant synthesis by combining textual interpretation with socio-psychological analysis. The novelty of this study lies in emphasizing nusyuz as a reciprocal issue that may occur on either side of the marital relationship, and in highlighting reconciliation (ṣulḥ), justice, and dialogical approaches as key mechanisms for conflict resolution. The study implies the need for tafsir perspectives that are responsive to contemporary family dynamics and support women’s rights in cases of marital neglect. Future research is encouraged to explore female exegetical perspectives and to conduct empirical studies on the implementation of husband nusyuz in mediation practices and religious court proceedings.